Global apparent temperature sensitivity of terrestrial carbon turnover modulated by hydrometeorological factors - Fan, Naixin (2022)
We are in debt to FLUXNET principal investigators and researchers for the fundamental measurements and synthesis datasets used to build the upscaled and in situ flux datasets used in this study. The work used eddy covariance data from La Thuile Synthesis Dataset, which were provided by the FLUXNET community. In particular, we thank A. Altaf, J. Beringer, P. Blanken, C. Brümmer, S. Burns, J. Cleverly, E. Cremonese, T. Grünwald, P. Kolari, W. Jans, M. Leonardo, T. Manise, M. Mund, A. Noormets, E. Pendall, C. Pio, S. Prober, L. Šigut, A. Varlagin and W. Woodgate, who provided us with site-level measurements of soil carbon and vegetation biomass, and B. Amiro, J. Ardö, S. Arndt, D. Baldocchi, L. Belelli, F. Bosveld, D. Bowling, N. Buchmann, A. Christen, M. Cuntz, A. Desai, B. Drake, I. Goded, A. Goldstein, C. Gough, S. Ivan, L. Hutley, I. Janssens, M. Karan, H. Kobayashi, M. Korkiakoski, B. Kruijt, S. Linder, B. Loubet, I. Mammarella, S. Minerbi, W. Munger, Z. Nagy, D. Papale, A. Richardson, B. Ruiz, E.P. Sanchez-Canete, FCE. Silva, E. Veenendaal, S. Wharton, G. Wohlfahrt, J. Wood, D. Yakir and D. Zona, who provided contacts and/or references for us to find site-level measurements of soil carbon and vegetation biomass. We are thankful to S. Bao and S. Besnard for helping with collected and processed site-level FLUXNET and vegetation biomass data. We thank M. Migliavacca and M. Schrumpf for providing reference and useful resources for data collection. N.F. acknowledges support from the International Max Planck Research School for Global Biogeochemical Cycles. Publisher Copyright: © 2022, The Author(s).